Using APIs for Data Collection on Social Media - Lomborg, Stine; Bechmann, Anja (The Information society, 2014)
This article discusses how social media research may benefit from social media companies making data available to researchers through their application programming interfaces (APIs). An API is a back-end interface through which third-party developers may connect new add-ons to an existing service. The API is also an interface for researchers to collect data off a given social media service for empirical analysis. Presenting a critical methodological discussion of the opportunities and challenges associated with quantitative and qualitative social media research based on APIs, this article highlights a number of general methodological issues to be dealt with when collecting and assessing data through APIs. The article further discusses the legal and ethical implications of empirical research using APIs for data collection.